2023
DOI: 10.3390/vaccines11020350
|View full text |Cite
|
Sign up to set email alerts
|

Tixagevimab and Cilgavimab (Evusheld™) Prophylaxis Prevents Breakthrough COVID-19 Infections in Immunosuppressed Population: 6-Month Prospective Study

Abstract: Background: Persons with neuroinflammatory diseases (pwNID) treated with potent immunosuppressives are at risk of severe COVID-19 outcomes and reduced vaccine seroconversion. We aimed at determining the real-world efficacy of tixagevimab and cilgavimab (Evusheld™) in immunosuppressed pwNID in preventing breakthrough COVID-19 infections. Methods: 31 immunosuppressed pwNID were followed for 6 months after administration of tixagevimab and cilgavimab as a prophylactic COVID-19 medication (January 2022–July 2022).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…To our knowledge, this is the first prospective study that followed the patients with AAV after tixagevimab/cilgavimab administration. Our data confirm a good safety profile and potential efficacy of tixagevimab/cilgavimab in immunosuppressed AAV patients and are consistent with previously published studies (6)(7)(8). The limitations of our study include a small sample size, absence of a control group and administration of tixagevimab/ cilgavimab at a lower dose than currently recommended.…”
Section: Sirssupporting
confidence: 90%
“…To our knowledge, this is the first prospective study that followed the patients with AAV after tixagevimab/cilgavimab administration. Our data confirm a good safety profile and potential efficacy of tixagevimab/cilgavimab in immunosuppressed AAV patients and are consistent with previously published studies (6)(7)(8). The limitations of our study include a small sample size, absence of a control group and administration of tixagevimab/ cilgavimab at a lower dose than currently recommended.…”
Section: Sirssupporting
confidence: 90%
“…A systematic review and meta-analysis of the protective properties of the monoclonal antibody combination, including patients with hematological malignancies in the Omicron era, also highlighted its clinical effectiveness [ 50 ]. A 6-month prospective study on 31 immunocompromised patients receiving immunosuppressive therapy reported that Evusheld significantly reduced the severity of breakthrough COVID-19 infections during the BA.4 and BA.5 Omicron wave [ 51 ]. A single-center retrospective study analyzing clinical outcomes of patients with hematological malignancies who were administered tixagevimab/cilgavimab for COVID-19 prevention or treatment generated beneficial results [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown the reduced neutralization ability of tixagevimab–cilgavimab to Omicron BA.1 and BA.2, and even more reduced neutralization to recent variants such as BQ 1.1 and XBB 1.5 [ 119 ]. Another in vitro study showed that, while tixagevimab–cilgavimab continued to inhibit BA.2.12.1, BA.4, and BA.5, the titers needed to achieve an equivalent level of inhibition (50% neutralization) for BA.5 were approximately 30.7 times higher than those required for the ancestral strain [ 120 ]. Nevertheless, the previously mentioned clinical data continued to demonstrate the effectiveness of tixagevimab–cilgavimab during the Omicron wave [ 112 , 113 , 114 , 115 ].…”
Section: Pre-exposure Prophylaxismentioning
confidence: 99%